2003
DOI: 10.1002/ajmg.a.10102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing for a BRCA1 mutation: Prophylactic surgery and screening behavior in women 2 years post testing

Abstract: Mutations in the BRCA1 gene are associated with an increased risk of breast and ovarian cancer in carrier women. An understanding of behavioral responses to BRCA1 mutation testing by mutation carriers and non-carriers is important to guide the clinical application of this new technology. This study examined the utilization of genetic testing for a BRCA1 mutation in high-risk individuals and the response of tested women with respect to interventions for early cancer detection and prevention. This study assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
131
2
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 39 publications
23
131
2
3
Order By: Relevance
“…Previous studies, which focused on the effects of revealing genetic susceptibility information to individuals with high family risk profiles for diseases have shown a mix of negative, positive, and null findings. [18][19][20][21][22][23][24][25][26] Even among DTC customers, previous research suggested that the population effects of such reports are largely insignificant but individuals may experience adverse emotional effects after learning about certain specific diseases' susceptibilities. 29 In an effort to draw causal inferences, this study supplemented previous research such as the REVEAL study, 20,24 which used a randomized block experimental design, to explore effect of learning about one's own genetic susceptibility to diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies, which focused on the effects of revealing genetic susceptibility information to individuals with high family risk profiles for diseases have shown a mix of negative, positive, and null findings. [18][19][20][21][22][23][24][25][26] Even among DTC customers, previous research suggested that the population effects of such reports are largely insignificant but individuals may experience adverse emotional effects after learning about certain specific diseases' susceptibilities. 29 In an effort to draw causal inferences, this study supplemented previous research such as the REVEAL study, 20,24 which used a randomized block experimental design, to explore effect of learning about one's own genetic susceptibility to diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Some researchers suggest that increased disease risk, which may be rooted in genetic susceptibility information, should increase vigilant behaviors. 40 Others have pointed out that the increased fatalism that often accompanies genetic attributions may reduce vigilant behaviors as the genetic influence is interpreted as destiny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54,97-100 Despite increased public awareness, recent studies still reflect low rates of BRCA1/BRCA2 carriers opting for prophylactic mastectomies (range, 0%-37%). [101][102][103] The majority of individuals opt for and use regular surveillance.…”
Section: Hbocmentioning
confidence: 99%
“…[101][102][103] RRBSO is now considered the optimal risk-management strategy for this population of high-risk women. [19][20][21][22] Choosing RRBSO appears to be related to older age, perceived cancer risk, and perceived benefit of surgery.…”
Section: Hbocmentioning
confidence: 99%